Use of Information Technology in the Management of Higher Education Institution - Shorobura, Inna (Pedagogical Discourse, 2016)
The theoretical aspects of information technology in the management of higher education institution have been revealed in the article. General trend of informatization of education, including higher education have been shown. Priority areas for its implementation and design management have been reveals. The attention on creating educational space information on implementation in higher education methods, means of information and communication technology and computer technology-oriented activities. The peculiarities of information management, information resources and information management technologies. The development of information management systems linked to the organization of data and knowledge consistent to their development of integrated automated control systems of higher education institution. Thesis there is determined directions of introduction of ICT in the management of the institution, including the provision of opportunities for future professionals of education using ICT during training. In particular, the provision of computer and information literacy, primarily through the establishment of the education system, including higher education, focused on the use of new information and communication technologies in the formation of fully developed personality. Focused on creating the conditions for computer and information literacy of all employees of university, a system of motivations regarding the implementation and use of ICT to create broad demand for such technologies in the training. along with technological aspect of information institutions of higher education, program implementation is impossible without a developed system of information services. An important role in this process is played by universities information sites. They have to become not only sources of information about the activities of the institution, but also a means of communication and integration in the information space. Oriented well as the formation of information culture of students; creating new and additional conditions for improving the quality of education; development of new forms of education and learning technologies based on ICT; of automated control systems at all organizational levels of the education system and at different types of schools; enhance coordination, efficiency and manageability, providing extraterritoriality and internationalization sciences research. Key words: higher education institution management, information technology, information and education space, information management.